The role of fructose-1,6-bisphosphatase 1 on regulating the cancer progression and drug resistance - Mengmeng Wang; Xiaoju Huang; Dan Zhang; Yisan Liu; Pian Liu (Discover Oncology)
Abstract Fructose-1,6-bisphosphatase 1 (FBP1) is the enzyme that limits the process of gluconeogenesis as it facilitates the hydrolysis of fructose-1,6-bisphosphate(F-1,6-BP) to produce fructose-6-phosphate(F6P) and inorganic phosphate. Gluconeogenesis is the production of glucose from small carbohydrate substrates. The gluconeogenic process is typically suppressed in cancer because it inhibits glycolysis. Apart from its involvement in cellular glucose metabolism, FBP1 also plays a role in gene transcription, mRNA translation and stability regulation, and the immune microenvironment of tumors. Because of its multifaceted functions, the mechanisms by which FBP1 is involved in tumor development are complex. Moreover, FBP1 deficiency is associated with radiation and chemotherapy resistance and poor prognosis in cancer patients. Restoration of FBP1 expression in cancer cells is expected to hold promise for cancer therapy. However, up to now few reviews have systematically summarized the important functional mechanisms of FBP1 in tumorigenesis and the small molecule compounds that restore FBP1 expression. Therefore, this article addresses the question “How does FBP1 contribute to cancer progression, and can targeting FBP1 be a potential therapeutic approach?” by summarizing the effects of FBP1 on cancer development and progression as well as its mediated drug resistance and the future clinical applications of potential small molecule modulators targeting FBP1.